Study of Moinuddin jovini's Prose style in Developmental Stylistic Point of View - Narges Rezvani Moghadam; Iraj Mehraki; Azar Daneshgar (مطالعات زبانی و بلاغی)
The science of stylistics is one of the sciences of Persian literature that does not have a long history. This knowledge in Iran also begins scientifically with the research of Mohammad Taghi Bahār. For some writers, stylistics is the only way that can scientifically show the individual differences between poets and writers and describes and expresses the author through the study and analysis of lexical features, syntax, sentence structure, virtual language, linguistic body. In European literature, too, the German Leo Spitzer is one of the stylists who has theorized in this field. In stylistic research, style is divided into three types: periodic, literary, personal and developmental. This study intends to examine the personal style of Moinuddin Jovayni in the Negarestan. Although this work is also written in the way Golestan Saadi(saʿdi); But in any case, each author has his own style that is unique. The research method is descriptive and analytical. The research findings show that Jovayni has used a special method in expressing mystical, moral, religious, etc. issues in the field of linguistic, literary and thought that distinguishes his personal style from other writers.